Utilization of Western Medicine and Traditional Chinese Medicine Services by Physicians and Their Relatives: The Role of Training Background - Huang, Nicole (Hindawi Publishing Corporation, 2011)
Despite extensive efforts to improve the attitude and practice of physicians with respect to complementary and alternative medicine (CAM), the role of training background on physician's own utilization of mainstream Western medicine (WM) and CAM remains unclear. We aimed to compare personal utilizations of WM and traditional Chinese medicine (TCM) among doctors trained in WM only, TCM only or both. A retrospective population-based study was conducted using the 2004 Taiwan's National Health Insurance data. A total of 103 879 doctors and their relatives and 2 623 658 other adults with equivalent socioeconomic status were analyzed. Ambulatory care utilization of WM and TCM services was compared using the following three measures: probability of any use, number of visits and total annual expenditure. Doctors who were trained in Western medicine only (WMDs) had the highest WM use, followed by doctors who were trained in both (WMD-CMDs), while Chinese medicine-trained doctors (CMDs) had the lowest use. For TCM use, a reverse pattern was observed. Similar patterns were found among doctors' relatives. Compared with other adults with equivalent socioeconomic status, both the CMDs and WMD-CMDs had a greater use of TCM services. For WM, although the WMDs' probability and frequency of usage were similar to other adults, they incurred considerably higher expenditure. The use of WM and TCM by doctors and their relatives was significantly associated with the training background of the doctors. This highlights the importance of how increasing knowledge and understanding of other medical discipline may influence a practitioner's care-providing behaviors.